Autobiografie televisive: un'analisi della performance spettatoriale (Mantichora. Italian Journal of Performance Studies, 2020)
In the age of “mobile” media, characterized by personalization, relocation and desynchronization of everyday life, the centrality of television in the contemporary experience is yet indisputable. The purpose of this paper, through the reading of biographical diaries of six young women born between 1973 and 1990, is to interpret television programs as generators of mobility in terms of emotions, space and time. We will show how the static nature of television’s “hardware” is compensated by means of the mobility allowed by a “software” made of texts that multiply the spaces in which it is possible to live.